Modeling heat transfer in fluid flow near a decelerating rotating disk with variable fluid properties. (July 2020) - Rafiq, Talat; Mustafa, M.; Farooq, M. Asif
Abstract: Present work formulates the unsteadily revolving fluid flow caused by a rotating porous disk in a variable viscosity fluid. Following an existing paper, the disk angular velocity is assumed to exhibit an inversely linear time dependency. Moreover, temperature dependency in fluid viscosity is incorporated in the analysis. Two different numerical approaches namely, a modified finite difference scheme and the collocation method based MATLAB package bvp4c, are employed to find self-similar solutions. Subtle fluid mechanics concepts such as radial wall stress, torque required, volumetric flow rate and heat transfer rate are analyzed for full range of unsteadiness parameter S, measuring the decay rate of disk angular velocity. There exists a particular value of S designated as S ∗ which corresponds to zero torque ( G ′(0) = 0) illustrating the situation of freely rotating disk. Beyond this value of S, that is S < S ∗, G ′ (0) has a negative sign signaling that fluid's angular velocity becomes higher than that of the disk. Our emphasis is to seek how the said flow model is affected by variable fluid properties. It should be remarked here that variable viscosity/thermal conductivity considerably alters the overall drag coefficient as well as heat transfer rate.